A review of genetic algorithm application in examination timetabling problem - Mohammed M.A.; Ghani M.K.A.; Obaid O.I.; Mostafa S.A.; Ahmad M.S.; Ibrahim D.A.; Burhanuddin M.A. (Medwell Journals, 2023)
Many studies have used different types of genetic algorithm in solving examination timetabling problem. The solutions of the genetic algorithm are found to be efficient and reliable. This study provides a comprehensive review of genetic algorithm application in examination timetabling. It presents many examples of using genetic algorithm in finding optimal solutions to the problem of examination timetabling at universities or institutions. Subsequently, it presents the most used techniques to solve the examination timetabling problem such as tabu search and simulated annealing techniques. The objective of the study is to provide an understanding on what have been achieved in solving examination timetabling problem. Medwell Journals, 2017.